Analysis of the Profit Sharing System Between Ship Owners and Fishermen from an Islamic Economic Perspective in the Pangkajene - Amelia Pratiwi (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This study examines the practice of a profit-sharing system between boat owners and fishermen from the perspective of Islamic economic law and its implications for the economic well-being of both parties. This research uses a qualitative approach in the Pangkajene area, a coastal area in South Sulawesi, with a socio-economic perspective and is based on the Sharia Enterprise Theory, which integrates Islamic values ​​into economic analysis, making it transcendental and human-oriented. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, presentation, and conclusion-drawing techniques. The findings indicate that a 50:50 profit-sharing system is implemented between boat owners and fishermen. From an Islamic perspective, this practice falls under the mudharabah contract, which fulfills important elements such as contracting parties, the object of the contract, offer and acceptance, and the profit-sharing ratio. This system is considered fair because it does not disadvantage either party and reflects the principles of justice and cooperation. The application of the mudharabah contract in profit-sharing practices has been shown to improve the welfare of both fishermen and boat owners, while strengthening the role of boat owners as capital providers and drivers of the local economy.